Association of antiviral prophylaxis and rituximab use with posttransplant lymphoproliferative disorders (PTLDs): A nationwide cohort study. Issue 7 (22nd December 2020) - Walti, Laura N.; Mugglin, Catrina; Sidler, Daniel; Mombelli, Matteo; Manuel, Oriol; Hirsch, Hans H.; Khanna, Nina; Mueller, Nicolas; Berger, Christoph; Boggian, Katia; Garzoni, Christian; Neofytos, Dionysios; et al.
Abstract: Posttransplant lymphoproliferative disorder (PTLD) is a serious complication of solid organ transplantation (SOT). Most PTLD cases are associated with Epstein–Barr virus (EBV) infection. The role of antiviral prophylaxis or rituximab therapy for prevention of PTLD in SOT recipients is controversial. In a nationwide cohort, we assessed the incidence, presentation, and outcome of histologically proven PTLD. We included 4765 patients with a follow‐up duration of 23 807 person‐years (py). Fifty‐seven PTLD cases were identified; 39 (68%) were EBV positive (EBV+ PTLD). Incidence rates for EBV+ PTLD at 1, 2, and 3 years posttransplant were 3.51, 2.24, and 1.75/1000 py and 0.44, 0.25, and 0.29/1000 py for EBV− PTLD. We did not find an effect of antiviral prophylaxis on early and late EBV+ PTLD occurrence (early EBV+ PTLD: SHR 0.535 [95% CI 0.199–1.436], p  = .264; late EBV+ PTLD: SHR 2.213, [95% CI 0.751–6.521], p  = .150). However, none of the patients (0/191) who received a rituximab‐containing induction treatment experienced PTLD, but 57 of 4574 patients without rituximab induction developed PTLD. In an adjusted restricted mean survival time model, PTLD‐free survival was significantly longer (0.104 years [95% CI 0.077–0.131]) in patients receiving rituximab as induction treatment. This study provides novel data on the association of rituximab induction and reduced risk for PTLD. Abstract : In this nationwide cohort study of solid organ transplant recipients, rituximab given as part of the induction regimen, in contrast to antiviral prophylaxis, is associated with a lower incidence of posttransplant lymphoproliferative disorders.